Budget Institutions and Government Effectiveness - Momi Dahan; Michel Strawczynski (Center for Economic Studies and ifo Institute (CESifo), 2016)
Do budget institutions play a role in explaining why government effectiveness is higher in some advanced countries than in others? Employing an original panel dataset that spans four different years (1991, 2003, 2007 and 2012) we find that budget centralization has a negative and significant effect on government effectiveness in OECD countries after accounting for a list of control variables such as GDP per capita and government expenditure in addition to country and year fixed effects. We show that less centralized countries display significant better performance in health and infrastructure but similar effectiveness in tax collections. The negative impact of budget centralization seems to bite especially at the execution stage of the budgeting process, while it is not significant at the formulation and legislation stages. These results survive a list of sensitivity tests.
Keywords: H11; H61; 330; government effectiveness; budgeting process; bureaucratic autonomy